2021
DOI: 10.1108/cdi-09-2020-0248
|View full text |Cite
|
Sign up to set email alerts
|

Advancing employability: applying training evaluation to employability development programs

Abstract: PurposeThis paper aims to apply training evaluation to employability development, providing a systematic process to assess employability development programs' effectiveness under the framework of employability capital resources (Peeters et al., 2019).Design/methodology/approachThe authors demonstrate the training evaluation process within an employability development program for US secondary school students. This process included providing validation evidence for measures of evaluation criteria across multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Hiring what previous studies have highlighted (Galvão et al, 2020;Glerum and Judge, 2021;Kravariti and Johnston, 2020;McWilliams et al, 2022), the existence of continuing training programs does not impact the achievement of the results desired by organizations. In four of the six organizations, training in the area of risk management, when carried out by professionals, is not sufficient to optimize the results of the organization, because according to the managers of five organizations, there is no type of metric to assess the application of knowledge acquired by the employees who carry out the training.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Hiring what previous studies have highlighted (Galvão et al, 2020;Glerum and Judge, 2021;Kravariti and Johnston, 2020;McWilliams et al, 2022), the existence of continuing training programs does not impact the achievement of the results desired by organizations. In four of the six organizations, training in the area of risk management, when carried out by professionals, is not sufficient to optimize the results of the organization, because according to the managers of five organizations, there is no type of metric to assess the application of knowledge acquired by the employees who carry out the training.…”
Section: Discussionmentioning
confidence: 90%
“…Scholars argue that continued training in risk management causes impact on organizations' results (Galvão et al, 2020;Glerum and Judge, 2021;Kravariti and Johnston, 2020;McWilliams et al, 2022). However, this research concluded that the training component does not affect the achievement of the results desired by the organization.…”
Section: Conclusion Limitations and Further Researchmentioning
confidence: 87%
See 1 more Smart Citation
“…Glerum and Judge [19] believed that education and training can provide employees with employment skills and support their development. If the enterprise conducts education and training regularly, its overall benefits will be revealed.…”
Section: Corporate Sustainable Trainingmentioning
confidence: 99%
“…Similarly to training activities for villagers, the effort of training evaluation becomes crucial to assess the effectiveness, efficiency of the training program, or both. This is necessary to make decisions on whether to further invest in the program [40]. Hence, the results of the program evaluation determine the continuity of activities.…”
Section: Introductionmentioning
confidence: 99%